Creating a violin orchestra in pre-school education: Voices of hope - Davys Moreno (2022)
Early Childhood Education in Portugal and Chile is considered the first stage of Basic Education in the process of lifelong education. To overcome the artistic-musical limitations of Kindergarten Educators, an Intervention Project was developed in Chile between 2011 and 2013, in 3 kindergartens of the network of the Junta Nacional de Jardines Infantiles de Chile, which included a Music Training Programme. The aim of this Training Programme was to improve the music skills of 18 educators, including learning the violin instrument through the methodology of Doctor Shinishi Suzuki. After the completion of this Training Programme, the Educators replicated the knowledge obtained with the children to learn the violin instrument. The present study aims to evaluate the results obtained in the Intervention Project. To this end, two questionnaire surveys were prepared and validated, aimed at the Kindergarten Educators and the Parents and Guardians of the children involved. From the analysis of the answers obtained, it was concluded that the Kindergarten Educators consider that they developed good collaborative work, improved the coexistence and sharing of knowledge, learned new methodologies, through significant learning, including the learning of the violin, and the incorporation of music in their activities with the children. They felt valued as people and that others believed in them as professionals. They were able to learn and replicate the knowledge acquired and felt they produced an improvement in the children's developmental areas, which was also recognised by the parents.  Finally, this study is a real contribution to validate this type of projects by showing that if we enhance the skills of Early Childhood Educators in Music, they can replicate their knowledge with the children they work with. Future projects of this type may be replicated, in other contexts, namely in Portugal.